Investigating the contribution of hop components to the perception of beer flavour - Dietz, Anna Christina (2022)
Considering the substantial amount of research that has been published in the field of hop science during the last decades, very little is known with regard to the multimodal flavour perception of hop-derived volatiles that not only contribute to the pleasant ‘hoppy’ aroma and flavour, but are also involved in other sensations of gustatory and trigeminal origin perceived in beer. The aim of this research was to further understand the sensory complexity of Magnum hop essential oil and scCO2 hop oil fractions extracted therefrom. This PhD project combined static and dynamic sensory techniques, an established gas chromatographic method, and comprehensive statistical analyses to investigate the relationship between hop volatile compounds and their sensory characteristics (quantitative and qualitative) in different matrices.